1978
DOI: 10.1111/j.1439-0329.1978.tb01466.x
|View full text |Cite
|
Sign up to set email alerts
|

Die gegenwartige Epidemie des Tannensterbens.

Abstract: The present epidemic of dying of silver fir. Its geographical distribution in the northern part of the natural distribution of Abies alba. Dying of silver fir, a complex disease phenomenon of Abies alba which has recurred periodically for more than a century and which is still unexplained, has been especially serious in recent years north of the Alps. Based on disease symptoms in the crowns, the present distribution of the disease is shown and described on a map. The necessity for increased international coope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
5

Year Published

1980
1980
1995
1995

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 1 publication
0
2
0
5
Order By: Relevance
“…In 1983, studies were initiated to determine if damage symptoms of Abies alba at various diseased forest sites in Europe (Schütt, 1978;Bauch et a1., 1979;Berchtold et a1., 1981;Schweingruber et al, 1983;Eckstein et al, 1983;Torelli et al, 1986, this issue) could be identified in A. balsamea growing on spruce-fir sites of the northeastern Uni ted States. Declining periodic growth rate was observed in balsam fir stands ac ross northern New England, including stands with and without the impact of spruce budworm (Choristoneura [umi[erana) defoliation (Blanchard et a!., 1983).…”
Section: Introductionmentioning
confidence: 99%
“…In 1983, studies were initiated to determine if damage symptoms of Abies alba at various diseased forest sites in Europe (Schütt, 1978;Bauch et a1., 1979;Berchtold et a1., 1981;Schweingruber et al, 1983;Eckstein et al, 1983;Torelli et al, 1986, this issue) could be identified in A. balsamea growing on spruce-fir sites of the northeastern Uni ted States. Declining periodic growth rate was observed in balsam fir stands ac ross northern New England, including stands with and without the impact of spruce budworm (Choristoneura [umi[erana) defoliation (Blanchard et a!., 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Seit vielen Jahren beobaehtet man in Europa einen Prozef?, der oft ,,Tannensterben" genannt wird. Diesem Thema wurden zahlreiche Veroffentliehungen gewidmet, deren Autoren auf versehiedene Faktoren aufmerksam machen, die ihres Er.ichtens die Tanne negativ beeinflussen und zu deren vorzeitigen Absterben beitragen (SCHUTT 1978). SZAFER (1920) vermutet, daS die Tanne in der gegenwartigen Periode naeh Siidwesten zuriickweicht.…”
Section: Introductionunclassified
“…Das Tannensterben, eine periodisch wiederkehrende Komplexkrankheit der Weifitanne {Abies alba Mill.) fiihrt derzeit nordlich der Alpen zu Ausfalien bedrohlichen Umfangs (SCHUTT 1978). Wahrend iiber die Krankheitssymptome in Eiteratur und forstlicher Praxis Einigkeit besteht, gehen die Auffassungen iiber die Krankheitsursachen weit auseinander (SCHUTT 1977;WACHTER 1978).…”
Section: Introductionunclassified
“…fiihrt derzeit nordlich der Alpen zu Ausfalien bedrohlichen Umfangs (SCHUTT 1978). Wahrend iiber die Krankheitssymptome in Eiteratur und forstlicher Praxis Einigkeit besteht, gehen die Auffassungen iiber die Krankheitsursachen weit auseinander (SCHUTT 1977;WACHTER 1978). Eediglich die Mitwirkung von Diirreperioden als krankheitsauslosendes oder -verstarkendes Ereignis wird von den meisten Autoren akzeptiert.…”
Section: Introductionunclassified
See 1 more Smart Citation